Estudio de costos para servicios ofertados por el CTEC bajo el eje de vinculación empresarial para los sectores productivos de la Región Huetar Norte - Sánchez-Ugalde, Christian (Instituto Tecnológico de Costa Rica, 2015)
This research was conducted in order to provide the CTEC a cost structure of the services offered under the aegis of corporate engagement in particular those services such as trainings, bromatological analysis of fodder and program update for SMEs (small and medium-sized enterprises) with the Project Odoo. The cost model for activity contains information relevant to the administration of CTEC in decision-making at the time of budgeting one of these services or activities, contains each of elements and generators of costs incurred by each activity. The cost model for activity, is a tool that can be used both by the administration of CTEC, headquarters staff or employers in the región who are interested to make use of these services. It is also a basis for developing a web app that allows the user to perform the same Budget in order to streamline this process.
Proyecto de Graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica, Escuela de Administración de Empresas, 2015.
Keywords: Costos; Producción; Servicios